Archaeal genetics – the third way - Allers, Thorsten; Mevarech, Moshe (Nature Publishing Group, 2005)
For decades, archaea were misclassified as bacteria on account of their prokaryotic morphology. Molecular phylogeny eventually revealed that archaea, like bacteria and eukaryotes, are a fundamentally distinct domain of life. Genome analyses have confirmed that archaea share many features with eukaryotes, particularly in information processing, and therefore can serve as streamlined models for understanding eukaryotic biology. Biochemists and structural biologists have embraced the study of archaea but geneticists have been more wary, despite the fact that genetic techniques for archaea are quite sophisticated. It is high time for geneticists to start asking fundamental questions about our distant relatives.